MRI Assessment of Cardiac Function and Morphology in Adult Patients With Growth Hormone Deficiency: A Systematic Review and Meta-Analysis - Bioletto, Fabio; Prencipe, Nunzia; Berton, Alessandro Maria; Bona, Chiara; Parasiliti-Caprino, Mirko; Faletti, Riccardo; Ghigo, Ezio; Grottoli, Silvia; Gasco, Valentina (Frontiers in Endocrinology, 2022)
Background. Adult GH deficiency (GHD) has been described as a heterogeneous condition characterized by many clinical modifications, such as metabolic alterations, impaired quality of life, and increased mortality. The clinical relevance of cardiac involvement remains, however, only partially elucidated. Methods. PubMed/Medline, EMBASE, Cochrane library, OVID and CINAHL databases were systematically searched until February 2022 for studies evaluating cardiac function and morphology by magnetic resonance imaging in adult patients with GHD. Effect sizes were pooled through a random-effect model. Results. Four studies were considered in the meta-analysis. With respect to the left ventricle, GHD patients were characterized by a lower stroke-volume-index (-3.6 ml/m2, standardized mean difference (SMD) -0.60, 95%CI [-1.15,-0.05], p=0.03), lower end-diastolic-volume-index (-6.2 ml/m2, SMD -0.54, 95%CI [-0.97,-0.10], p=0.02) and, after accounting for possible biases, lower mass-index (-15.0 g/m2, SMD -1.03, 95%CI [-1.89,-0.16], p=0.02). With respect to the right ventricle, a lower end-diastolic-volume-index (-16.6 ml/m2, SMD -1.04, 95%CI [-2.04,-0.03], p=0.04) and a borderline-significant lower stroke-volume-index (-5.0 ml/m2, SMD -0.84, 95%CI [-1.77,0.08], p=0.07) could be observed. Data about the effect of GH replacement therapy highlighted a significant increase in left ventricular mass-index after treatment initiation (+3.7 g/m2, 95%CI [1.6,5.7], p<0.01). Conclusion. With respect to the left ventricle, our results confirmed those retrieved by echocardiographic studies. In addition, significant alterations were demonstrated also for the right ventricle, for which echocardiographic data are nearly absent. This supports the thesis of a biventricular cardiac involvement in patients with GHD, with a similar pattern of morphological and functional alterations in both ventricles.